2013
DOI: 10.1002/chem.201301067
|View full text |Cite
|
Sign up to set email alerts
|

Oxo–Group‐14‐Element Bond Formation in Binuclear Uranium(V) Pacman Complexes

Abstract: Simple and versatile routes to the functionalization of uranyl-derived U(V)-oxo groups are presented. The oxo-lithiated, binuclear uranium(V)-oxo complexes [{(py)3LiOUO}2(L)] and [{(py)3LiOUO}(OUOSiMe3)(L)] were prepared by the direct combination of the uranyl(VI) silylamide "ate" complex [Li(py)2][(OUO)(N")3] (N" = N(SiMe3)2) with the polypyrrolic macrocycle H4L or the mononuclear uranyl (VI) Pacman complex [UO2(py)(H2L)], respectively. These oxo-metalated complexes display distinct U-O single and multiple bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…5 8 4 , 2 . 6 1 5 Å ) 2 32 The U−N bonds of 2.504(6), 2.529(6), and 2.547(6) Å for the pyridine(diimine) ligands are much longer than those in 1, supporting three dative bonding interactions. 18 However, ligand reduction is apparent by examining the intraligand distances for the pyridine ring.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 97%
“…5 8 4 , 2 . 6 1 5 Å ) 2 32 The U−N bonds of 2.504(6), 2.529(6), and 2.547(6) Å for the pyridine(diimine) ligands are much longer than those in 1, supporting three dative bonding interactions. 18 However, ligand reduction is apparent by examining the intraligand distances for the pyridine ring.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 97%
“…[2][3][4][5][6][7] For example, Arnold and co-workers demonstrated that sequential reaction of U VI O 2 (THF)(H 2 L) (L = polypyrrolic macrocycle) with KN(SiMe 3 ) 2 and FeI 2 resulted in formation of the U(V) silyloxide, [U V O(OSiMe 3 )(THF)Fe 2 I 2 L]. 7 Similarly, our research group has demonstrated that reaction of U VI O 2 ( Ar acnac) 2 ( Ar acnac = ArNC(Ph)CHC(Ph)O, Ar = 3,5-t Bu 2 C 6 H 3 ), 8 with a mixture of B(C 6 F 5 ) 3 and HSiR 3 (R = Ph, Et), 9,10 or with Ph 3 SiOTf alone, 11 results in formation of the reductive silylation products, U V (OSiR 3 )(OB{C 6 11 respectively. In contrast to these oxo functionalization reactions, examples of complete oxo substitution remain rare.…”
Section: Introductionmentioning
confidence: 99%
“…Two seminal, coincident reports of the potassium‐reduced coordination polymer {[UO 2 (py) 5 ][KI 2 (py) 2 ]} ∞ ( A ) showed that anaerobic uranyl(V) complexes are stable against disproportionation; since then, significant advances have been made in isolating uranyl(V) complexes. The reductive oxo functionalization with Group 1, Group 2, d‐block, rare‐earth, actinide, and main‐group metals as well as silicon is also possible. The linearity of the f 1 uranyl also provides a rare opportunity in f‐block chemistry to control the orientation of the magnetic vector, and uranyl(V)/transition‐metal single‐molecule magnets have been made through this oxo‐bridging strategy .…”
Section: Figurementioning
confidence: 99%